Effectiveness of Use of Islamic Integrated Mathematics LKPD Using A Scientific Approach to Prepare Students for KSM - Millah, Zakiyah Nur; Maulidani, Muhammad (Proceeding International Conference on Religion, Science and Education, 2024)
This research aims to determine the level of effectiveness of the Islamic Integrated Mathematics Student Worksheet (LKPD) Using a Scientific Approach to Prepare Students for KSM Events, especially on fraction material for class VII students at MTs NU Raden Rahmat . This research is development research ( Research and Development ) using the 4D model and consists of 4 development stages, namely: the definition stage ( define ), the design stage ( design ), the development stage ( develop ), and the dissemination stage ( disseminate ) . At the development stage, a validation process and effectiveness test are carried out. The validity test was given to MTs mathematics teacher Raden Rahmat . At this stage, revisions are also carried out to produce valid media. This effectiveness test was carried out in class VII MTs NU Raden Rahmat using a research trial using a research instrument on the effectiveness of using LKPD. At the distribution stage, product trials were carried out and then KSM practice questions were given. The results of the development research show that the Islamic Integrated Mathematics LKPD Using a Scientific Approach to Prepare Students for KSM Events is included in the valid category as seen from the validity test score with an average value of 4.01. This LKPD is also considered effective as seen from the results of the effectiveness test with the effectiveness achievement score: From the response questionnaire, students obtained a score of 4.1 so it is classified as effective. Student activities in the learning process are effective with an average score of 3.95. The learning outcomes of MTs NU Raden Rahmat students are classified as effective with an average score of 4.6, with the average student achieving a minimum completion score of 75 with a percentage of 81%. From the KSM practice questions provided which consist of 10 questions, 70% of students can do the practice questions so that the LKP D can be used to prepare students for the KSM event.